Effect of external magnetic field on weld pool flow conditions in high-speed gas metal arc welding. (January 2016) - Wu, CS; Yang, Fengzhao; Gao, Jinqiang
In high-speed gas metal arc welding process, weld defects like humping bead and undercutting appear and the weld bead quality worsens when welding speed exceeds a critical value. The previous investigations have proved that the backward flowing molten jet with high momentum in the weld pool is responsible for the formation of humping bead in high-speed gas metal arc welding. In this study, an external electromagnetic field generator is developed to change and control the flow condition in the weld pool and suppress the occurrence tendency of the humping bead. Bead-on-plate welding experiments are performed on mild steel Q235 test-pieces, and the influences of the exerted magnetic strength on the arc behavior, the fluid flow inside the weld pool, the weld bead shape and the weld penetration and width are investigated. The reason why the external electromagnetic field can suppress the humping bead is explained. The results show that external magnetic field can remarkably adjust the weld pool fluid flow field and decrease the momentum of the backward flowing molten jet. Therefore, weld defects like humping bead and undercutting can be effectively suppressed, the quality of weld bead is remarkably improved, and the critical welding speed is notably increased.